2021
DOI: 10.3389/fpsyg.2021.631791
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred and Sixty-One Days in the Life of the Homopandemicus in Serbia: The Contribution of Information Credibility and Alertness in Predicting Engagement in Protective Behaviors

Abstract: COVID-19 pandemic is a long-lasting process associated with dynamic changes within society and in individual psychological responses. Effective communication of measures by credible sources throughout the epidemic is one of the crucial factors for the containment of the disease, and the official communication about pandemics is straightforwardly directed toward changes in behavior via engagement in (self-)protective measures. Calls for the adherence to these measures are aimed at the general population, but pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 58 publications
(97 reference statements)
2
13
0
Order By: Relevance
“…In addition, extremely low trust in communication sources and politicians or governmental institutions was present among young people, which is in line with the results of previous research (Džamonja Ignjatović et al, 2019). Previous research has shown that trust in these official sources of information in our country declined during the pandemic, which confirmed the assumption about the dynamic nature of trust in institutions and official sources of information during the outbreak (Lep et al, 2021). Contrary to the results of our study, a cross-national online survey conducted on representative samples from six jurisdictions in Asian and Western societies, showed that institutional trust (e.g., trust in government) may increase vaccine willingness and uptake, and reduce the negative impact of misinformation on vaccine willingness and uptake (Chen et al, 2022).…”
Section: Vaccination Status Of Aea Predicts Future Vaccination Behaviorsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, extremely low trust in communication sources and politicians or governmental institutions was present among young people, which is in line with the results of previous research (Džamonja Ignjatović et al, 2019). Previous research has shown that trust in these official sources of information in our country declined during the pandemic, which confirmed the assumption about the dynamic nature of trust in institutions and official sources of information during the outbreak (Lep et al, 2021). Contrary to the results of our study, a cross-national online survey conducted on representative samples from six jurisdictions in Asian and Western societies, showed that institutional trust (e.g., trust in government) may increase vaccine willingness and uptake, and reduce the negative impact of misinformation on vaccine willingness and uptake (Chen et al, 2022).…”
Section: Vaccination Status Of Aea Predicts Future Vaccination Behaviorsupporting
confidence: 84%
“…Adolescents and emerging adults perceive the pandemic and behave differently during the pandemic, while simultaneously facing the developmentally-specific challenges (Ilić et al;Lep et al, 2021). They were disadvantaged in terms of their education (Petrovic, 2021;Viner et al, 2020), impending changes in the economy (Lep & Zupančič, 2020), mental health issues (Power et al, 2020;Radanović et al, 2021;Racine et al, 2021), and social relationships (Orben et al, 2020), all of which were confirmed in the systematic review by Panchal et al (2021).…”
Section: Adolescents and Emerging Adults And Vaccination Against Covi...mentioning
confidence: 81%
See 1 more Smart Citation
“…The positive relation between mistrust in the system and desirable high involvement implies two novel notions on trust. First, the trust in the system, or the generalised trust could be observed as secondary to interpersonal trust, meaning that when generalised trust deteriorates, as our findings show it did during the pandemic (e.g., Han et al, 2021;Lep et al, 2021), the interpersonal trust (trust in physicians in the present study) can still be a resource for building up women's agency in the medical context. However, both the physician and the patient are social roles, and the stability of the healthcare system should not be reduced to or leaning on personal trust toward a particular physician.…”
Section: Misuse Of Women's Trust Within Paternalistic Modelmentioning
confidence: 49%
“…For this policy to be effective cooperation from its recipients (mostly laypeople) is necessary. The distinctive feature of vaccines as a medical procedure is that vaccines act at both the individual and community level, making the decision to vaccinate inherently social (Arnesen et al, 2018;Goldenberg, 2021), further (Lau et al, 2015), perceived social consensus and norms and others (De Visser et al, 2011;Oraby et al, 2014), perceived vaccine safety and efficacy (Lazarus et al, 2022), knowledge and subjective knowledge (Lep et al, 2021;Zingg & Siegrist, 2012). Behavioral frameworks were developed to highlight the importance of psychological factors for vaccination intention.…”
Section: Introductionmentioning
confidence: 99%